Evaluasi Prosedur Penyusunan Anggaran dan Penetapan Anggaran - Eni Kaharti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
Abstract This research aimed to identify the roles of budget as a means of planning, controlling, and decision making at a hotel company, namely VSSB. This research evaluated budgeting process using the guidelines of Anthony and Govindarajan (2011) and Nafarin (2013). Budgetary control was evaluated in two ways, namely: (1) evaluation of budget implementation, (2) evaluation of budget achievement. The evaluation of calculating cost of room sold is a basis for determining a selling price by giving discounts. Cost classification is required in deciding budget management (Supriyono, 1989). Costs are classified according to their purpose. The results of this research indicated that the procedure for making budget in VSSB 2018 was normatively in compliance with budgeting procedure. GOP generated by VSSB could be classified as low budget (below 40%). In Seminyak Bali, VSSB was regarded as a leader in the hotel business based on hotel competitor report. The simulation of the basic room costs in VSSB was already proper so that giving discounts would not result in loss. Keywords: budget, planning, controlling, decision making, cost classification, BEP analysis and CVP analysis.